2015
DOI: 10.1007/s11356-015-4094-6
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the bioavailability of cadmium in contaminated soil by dithiocarbamate chitosan as a new remediation

Abstract: Dithiocarbamate chitosan (DTC-CTS) was used as a new amendment for remediation of cadmium (Cd)-contaminated soils to reduce the Cd bioavailability. Arabidopsis thaliana was chosen as a model plant to evaluate its efficiency. It was found that DTC-CTS could effectively improve the growth of A. thaliana. The amount of Cd up-taken by A. thaliana could be decreased by as much as 50% compared with that grown in untreated Cd-contaminated soil samples. The chlorophyll content and the aerial biomass of Arabidopsis als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Arabidopsis thaliana ecotype 'Columbia' seeds, which had been sterilized using 3% (w/v) sodium hypochlorite, were kept in dark at 4 C for 2 days and germinated on an MS medium. 32 Aer 7 days, the seedlings were transferred to small pot each containing 250 g of sandy soil and water retention agents mixture that had been watered with MS nutrient solution and tap water until saturated. Five seedlings were planted in each pot and three replicas were prepared per treatment.…”
Section: Plant Growth Experimentsmentioning
confidence: 99%
“…Arabidopsis thaliana ecotype 'Columbia' seeds, which had been sterilized using 3% (w/v) sodium hypochlorite, were kept in dark at 4 C for 2 days and germinated on an MS medium. 32 Aer 7 days, the seedlings were transferred to small pot each containing 250 g of sandy soil and water retention agents mixture that had been watered with MS nutrient solution and tap water until saturated. Five seedlings were planted in each pot and three replicas were prepared per treatment.…”
Section: Plant Growth Experimentsmentioning
confidence: 99%
“…Immobilization can reduce the mobility and bioavailability of heavy metals through addition of remediation agents to contaminated soils. Researchers have reported that amendment with dithiocarbamate chitosan (DTC-CTS) is effective in immobilizing Cd and mitigating accumulation in plants (Yin et al 2015), and thus potentially alleviate the toxicity of Cd to plants. Phytoremediation is advantageous as it physically removes the heavy metal contaminant from the soil through accumulation in plant biomass.…”
Section: Responsible Editor: Elena Maestrimentioning
confidence: 99%
“…Various soil remediation techniques have been employed to reduce the risks associated with HMs e ux into soil, including soil removal and replacement, soil washing, phytoremediation, and in-situ immobilization (Bolan et al 2014;Yin et al 2015). From the view of being fast and economical, in situ immobilization is a well-known method.…”
Section: Introductionmentioning
confidence: 99%
“…From the view of being fast and economical, in situ immobilization is a well-known method. This method reduces the availability of metal ions through sorption, complexation, and precipitation using organic/inorganic amendments (Chauhan et al 2012;Tripathi et al 2018;Yin et al 2015).…”
Section: Introductionmentioning
confidence: 99%